On the Influence of Microstructure on the Corrosion Behavior of Fe–Mn–Al–Ni Shape Memory Alloy in 5.0 wt% NaCl Solution. Issue 2 (15th October 2020) - Frenck, Johanna-Maria; Vollmer, Malte; Mandel, Marcel; Krüger, Lutz; Niendorf, Thomas
Abstract : Herein the corrosion behavior of Fe–Mn–Al–Ni shape memory alloys characterized by different microstructures in a 5.0 wt% NaCl solution is investigated. Open circuit potential and potentiodynamic polarisation tests are conducted. Generally, Fe–Mn–Al–Ni shows corrosion properties being similar to pure iron. However, the polarization curves of single crystals indicate the presence of an unstable passive system. The corrosion damage is analyzed by means of optical microscopy and electron microscopy. It is revealed that polycrystalline samples consisting of two different phases induced by heat treatment, i.e., α‐phase and γ‐phase or β‐Mn phase and γ‐phase, are suffering a selective corrosion attack of the α‐phase and β‐Mn–phase, respectively. On the contrary, the single crystal seems to form a protective layer on the surface. Upon presence of stress‐induced martensite, a selective corrosion attack of γ′–martensite is observed. Abstract : Electrochemical corrosion tests focusing on Fe–Mn–Al–Ni shape memory alloy in different microstructural conditions are conducted. Generally, results reveal a corrosion behavior similar to pure iron. However, different kinds of corrosive attack depending on the prevailing phases are seen. A single crystalline condition shows traces of passivation.